Acoustic characteristics of continuously graded phononic crystals. (August 2019) - Zhang, X.H.; Qu, Z.G.; Tian, D.; Fang, Y.
Abstract: The sound absorption performance of a continuously graded phononic crystal (CGPC) is presented in this study. The specific acoustic resistance has a major influence on the specific acoustic impedance, which can be optimized to obtain a high sound absorption coefficient. From the perspective of impedance match and energy conservation, a modified characteristic specific acoustic impedance is defined to reflect the local impedance of the CGPC. Based on the modified characteristic specific acoustic impedance, the improvement in the sound absorption performance of the CGPC is analyzed by comparing it with that of a uniform phononic crystal (UPC). The analysis results demonstrate that the improved sound absorption performance of the CGPC results from the decreased primary reflected energy associated with the increased absorbed energy in the CGPC. In addition, the sound insulation performance of the CGPC is experimentally investigated and discussed. The minimum difference in the transmission losses between a CGPC and a UPC is observed to be approximately 4 dB. This superior sound insulation performance of the CGPC is attributed to the increase in the primary reflected energy and the dissipated energy in the CGPC despite the slight decrease in the secondary reflected energy.